THE ART OF THEATER IN EDUCATIONAL SCHOOL PROCESSES - L. Zyazyun (Academy of Cognitive and Natural Sciences, 2004)
The article deals with the problems of traditional pedagogies. The main point of its contents and the task of educational process is the aspect of school graduate personality modeling in the direction of personality forming in accordance with the given characterological qualities. To solve this problem the author examines the theatrical performance on whose basis the school theater is formed.